Forensic psychiatric assessment process and outcome in state patients in KwaZulu-Natal, South Africa - Houidi, A; Paruk, S; Sartorius, B (AOSIS, 2018)
Background: Individuals who were charged with a serious offence may be referred by courts for forensic psychiatric assessment. The court may declare them as state patients if they are found unfit to stand trial or not criminally responsible because of mental illness or defect. In forensic psychiatry practice, there may be challenges in the forensic psychiatric observation process, and discrepancies may occur between the clinician report and the court’s decision. Objectives: To describe elements of the forensic psychiatric observation and discuss the legal correlates associated with the admission of state patients. Method: A retrospective study of the forensic psychiatric observation records of 91 newly admitted state patients at a forensic unit in KwaZulu-Natal over a 3-year period. Results: A total of 71 state patients (78.02%) were found not fit to stand trial and 10 patients (10.99%) were not criminally responsible. Nine patients (9.89%) were fit to stand trial and criminally responsible but still declared state patients and 13 state patients (14.29%) did not commit a serious offence. There was correlation for diagnosis between the assessing and the treating psychiatrists. Conclusion: The findings of the forensic observation were not always considered by the courts. Individuals found fit to stand trial, those found criminally responsible and those who did not commit serious crimes were declared state patients.